Una aplicación de valores plausibles a la calificación de pruebas estandarizadas vía simulación (2016)
The use of Plausible Values in large scale standarized tests, develop the role of imputation when the reference framework is too large and each person can not adress the totality of the items in the production. In that case appleal to block design deﬁnition that ensures an appropiate share of individuals per item aiming that the framework is addressed smugly across the study population is necessary. In general the imputation methos consist in ﬁnd the posterior distribution of the feature latent that is associated to the individual hability, by weighting distribution that induces model item response theory and regression associated with some latent variables measured in the individual. This paper shows an example of simulation where you can easily see the advantages oﬀered by the method in the aggregate results of this particle scheme application